The Influence of Learning Motivation on Students' Eco-Literacy of Environmental Pollution Material - Alifah, Ihsaniatun Nur; Handayani, Rif'ati Dina; Sudarti, Sudarti (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
The motivation to learn, together with the implementation of the independent curricula and the Pancasila (P5), has to go hand in hand with the development of environmental literacy to raise conservation awareness. This study aims to assess the significant influence of learning motivation on students' environmental literacy, especially concerning environmental pollution. Data collection methods include questionnaires and observations. Surveys gather data, while observations allow for a direct understanding of the observed phenomenon or behaviour. The result of the regression test with a constant value of ∝ environmental literacy is 18.358, and the directional coefficient/βX is +0.775; the higher the motivation to learn, the higher the level of environmental literacy. The significance value obtained from the ANOVA test was 0.000, below the 0.05 threshold. This result indicates that the hypothesis tested demonstrates a statistically significant effect. Therefore, learning motivation has been shown to improve eco-literacy significantly. The research concludes that learning motivation is essential in the learning process, serving as a driving force that enhances students' engagement, understanding, and overall academic success so that it can improve students' eco-literacy.